2021
DOI: 10.1051/e3sconf/202131603020
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizers Application to Improve Growth of Maize and Soil Nutrients

Abstract: Conventional productivity improvement still relies on the use of inorganic fertilizers. The continuous use of inorganic fertilizers is not effective in supporting the improvement of soil health; therefore it is necessary to use environmentally friendly fertilizers such as bio fertilizers. A pot experiment was carried out to study the effect of bio fertilizers application method on growth of maize and soil nutrient (Ntotal and P-available). Randomized block design was used with nine treatments repeated three ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Both seed as well as soil application might have resulted in providing more inoculum for improved colonization as compared to seed or soil application alone. Fitriatin et al (2021) reported that, seed and soil application of biofertilizers improved growth of maize compared to single method of application.…”
Section: Discussionmentioning
confidence: 99%
“…Both seed as well as soil application might have resulted in providing more inoculum for improved colonization as compared to seed or soil application alone. Fitriatin et al (2021) reported that, seed and soil application of biofertilizers improved growth of maize compared to single method of application.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained may be due to nutrients being responsible for increased cell enlargement, cell division, growth and photosynthesis which increase plant growth (Yaseen et al, 2019). Bio fertilizers has a beneficial role in plant growth and nutrients uptake, as these organisms may positively affect their host plant, such as nitrogen fixation, production of growth-promoting substances or organic acids, enhancing nutrients uptake (Hassan et al, 2012 andFitriatin et al, 2021). On the other hand, the improving effect of using organic fertilizer on plant growth may be due to its role in soil amelioration which enhances water holding capacity and increases the availability of macro and micro elements in the soil around the roots system which in turn increases plant growth (Mulyati et al, 2021).…”
Section: -Vegetative Growth and Nutrients Concentrations At Grain Mil...mentioning
confidence: 99%
“…Biofertilizer is a characteristic information that can be applied as a supplement to, or as a substituent of synthetic manure in sustainable farming [4]. Bio composts are substances that contain live microorganisms that colonize the rhizosphere or within plants and invigorate plant development by expanding the stock of essential supplement accessibility and additionally animating objective plant development, when applied to seeds, plant surfaces, or soil [5]. Mycorrhizal advantageous interaction expands ingestion of certain components like phosphorus, nitrogen and micronutrients, further develops water take-up, produces chemicals, lessens harms brought about by ecological pressure, works on nature of soil total [6].…”
Section: Introductionmentioning
confidence: 99%